“ANALYSIS OF THE ACADEMIC USE OF WHATSAPP AND FACEBOOK IN THE DEVELOPMENT OF READING AND WRITING SKILLS BETWEEN TEACHER AND STUDENTS, AND AMONG STUDENTS AT FIFTH SEMESTER OF LANGUAGE CAREER AT UNACH, DURING THE ACADEMIC TERM 2018-2019” - Samaniego Cisneros, Alexis Gonzalo (2019)
Through the years, technology has been an accelerate process of evolution. This development has made easier communication and interaction among people around the world. The use of Social Networks is a clear example. Due to the multiple purposes in which they can be used, they became an important tool in the educational field. The focus of the study is to analyze how Facebook and WhatsApp are used academically to develop the reading and writing skills at Fifth Semester of the Languages Career at Unach. The research frames into the English-Methodology area and into the qualitative approach in a descriptive level. The ethnographic method was used as well. To collect the necessary information to the professors and students has applied a survey by the researcher. Through the survey, it was recognized that there was a low academical use of Facebook and WhatsApp among teachers and Students. The principal activities performed to develop the reading and writing skills are: reading academic articles related to the major, reviewing specialized pages and posts to learn English vocabulary, reply to questions in English, respond to others’ posts in English and share scientific information. The outcomes of the research could be useful to the English teachers and students to create new and interesting activities to improve their reading and writing skills by using Facebook and WhatsApp.